Is Brazil Different? : Risk, Dollarization, and Interest Rates in Emerging Markets - Holland, Marcio; Bacha, Edmar L.; Goncalves, Fernando M. (Washington, D.C. : International Monetary Fund, 2007)
We investigate the role of financial dollarization in the determination of real interest rates in emerging economies. In a simple analytical model, we show that a strategy of "dedollarizing" the economy, if it fails to address fundamental macroeconomic risks, leads to higher domestic real interest rates. We confirm this prediction in an empirical model, but find that the effect is small after controlling for the risks of dilution and default. Brazil provides a natural case study given its low degree of financial dollarization and very high real interest rates. The estimated model is unable to explain the high interest rate levels in the aftermath of Brazil's 1994 inflation stabilization. However, since the adoption in 1999 of inflation targeting and floating exchange rates, Brazil's real interest rates are gradually converging to the model's predicted values. The estimation also shows that further drops in Brazil's real interest rates could be achieved more effectively through improvements in fundamentals that lead to investment-grade status rather than through financial dollarization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet